Francesco Lumachi: contribution to the biography of a Florentine publisher of the Early Twentieth century - Giovanna Grifoni (Bibliothecae.it, 2021)
Francesco Lumachi, the small Florentine bookseller who made his debut on the Italian publishing scene in 1900, despite belonging to an entrepreneurial reality, that of booksellers-publishers, anchored more to the past than to the future, is considered to have inaugurated, together with the new century, the modern book. With intuition and audacity, he was the first to contribute to the notoriety of authors destined to impose themselves on the cultural scene for their innovative qualities, and with refined aesthetic taste he published volumes of typographical elegance and sometimes also of unconventional form. As a true “friend of books”, as he liked to define himself, he was also the storyteller of amusing bibliographical stories. A multifaceted figure who always remained shrouded in mystery, due to his shy and modest nature, his brief professional career with dramatic results, and the probable loss of his personal and work papers. In an attempt to fill the biographical gap, this contribution presents the results of archival research that, for the first time, digs into Francesco Lumachi’s family roots and his schooling, a background from which unpublished elements emerge and, at the same time, a range of questions susceptible to further investigation, together with personality traits that find points of contact in editorial and existential choices, such as inconsistencies and fascinations that can be justified by the historical context of reference. The work also avails itself of an iconographic collection, also partly unpublished, as evidence and proof of the topics dealt with.